Estimation of prepractice hydration status of National Collegiate Athletic Association Division I athletes - Volpe, S. L.; Poule, K. A.; Bland, E. G. (Journal of Athletic Training, 2009)
National Collegiate Athletic Association Division I athletes need to be educated about proper hydration techniques to prevent hypohydration and protect athletic performance or need to be encouraged to properly hydrate before practices. More men than women appeared to be hypohydrated before practice. Hydration status did not differ with different phases of the menstrual cycle, but confirmation of this finding is needed through comparison of urine specific gravity or plasma osmolarity within the same athletes at different times in their menstrual cycles.